Results of Adjuvant FOLFOX Regimens in Stage III Colorectal Cancer Patients: Retrospective Analysis of 667 Patients - DANE, FAYSAL (KARGER, 2013)
Objective: The aim of this study was to assess the use of 5-fluorouracil (5-FU), leucovorin and oxaliplatin (FOLFOX) regimens in clinical practice according to their efficacy and toxicity. Methods: Patients who received oxaliplatin-containing regimens after curative resection for colorectal carcinoma from 10 different oncology centers between May 2004 and December 2009 were included in the study. All patients were treated with FOLFOX regimens. Patients with rectal carcinoma were also treated with chemoradiotherapy with 5-FU after 2 cycles of a FOLFOX regimen. Results: The median age of the patients was 56 years (range 17-78). Of the total 667 patients, 326 were given FOLFOX-4, 232 were given modified FOLFOX-4 and 109 were given FOLFOX-6. The distribution according to disease stage was 33 patients with stage IIIA colorectal cancer, 382 patients with stage IIIB and 252 patients with stage IIIC. The most common adverse events were neutropenia (54%), nausea (36.9%), neuropathy (38.2%) and anemia (33.1%) for all grades. The median follow-up time was 23 months (range 1-79). Three-year disease-free survival and overall survival were 65 and 85.7%, respectively. Conclusion: The different oxaliplatin-containing 5-FU-based adjuvant chemotherapy regimens in patients with stage III colorectal cancer seemed to be at least equal in terms of efficacy regardless of the method of 5-FU administration or oxaliplatin dose. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Colorectal adenocarcinoma; Adjuvant; Oxaliplatin; COLON-CANCER; MICROSATELLITE INSTABILITY; FLUOROURACIL; LEUCOVORIN; THERAPY; TRIAL; OXALIPLATIN; CARCINOMA; STATISTICS; SURVIVAL